Fat and fat‐free mass of healthy Swedish children show tracking during early life, but there are differences. (25th March 2019) - Forsum, E; Eriksson, B; Flinke, E; Henriksson, H; Henriksson, P; Löf, M
Abstract: Aim: Obesity may start early in life. We investigated relationships between size and body composition variables in infancy and at 4 years of age using valid estimates of body composition. The results were compared to those obtained when body mass index (BMI) was used to estimate body fatness at 4 years. Methods: Using air displacement plethysmography, size, fat mass and fat‐free mass were studied, between 2007 and 2015, in 253 full‐term healthy Swedish children at 1 week, 12 weeks and 4 years of age. Results: Positive associations between variables in infancy and at 4 years were found at 1 and 12 weeks for weight, height, BMI, fat‐free mass and fat‐free mass index (p ≤ 0.002) and for fat mass, per cent body fat and fat mass index (p ≤ 0.04) at 12 weeks. Fat mass gained during infancy correlated positively (p ≤ 0.031) with per cent fat mass, fat mass index and BMI, all at 4 years. In girls, gains in fat‐free mass during infancy correlated with BMI (p = 0.0005) at 4 years. Conclusion: The results provide information regarding body composition trajectories during early life and demonstrate limitations of BMI as a proxy for body fatness when relating early weight gain to variables, relevant for later obesity risk.